IMAGES CONSTRUCTIONS TECHNIC, PLANNING AND RISK REDUCTION: THE IMPLANTATION OF THE ERP’S SYSTEM IN A PUBLIC EDUCATIONAL INSTITUTION - Martins, Henrique Cordeiro; Martins, Maria Dalva; De Muylder, Cristiana Fernandes; Gonçalves, Carlos Alberto; Dias, Alexandre Teixeira (Revista de Administração da UFSM, 2013)
DOI: 10.5902/198346596327 This article describes the ERP planning and implementation process that includes identifying requirements,expectations, benefits, limitations and the ideational images built by the future users. The researchwas qualitative and quantitative descriptive based in the Instituto Federal Minas Gerais (IFMG) case:the first Brazilian public federal institution of technological education to install the ERP’s system. The datawas collected based on free and semi-structured interviews. The images configuration technic use allowedidentifying the user’s images for the ERP software. The positive images represented the success factors andthe negative images were related to aversion system implementation. Generally, the results indicated thatthe IFM’ ERP plans of implementation were propitious to build a unique identity. This paper aims also tocontribute with others studies related with ERP implementation in public organizations.